The Unique Existence of Weak Solution and the Optimal Control for Time-Fractional Third Grade Fluid System - Guangming Shao; Biao Liu; Yueying Liu (Complexity)
The paper concerns the third grade fluid system with the time-fractional derivative of the order α∈(0,1). We first establish unique existence criterion of weak solutions in the case that the dimension n=3. Then we prove the sufficient condition of optimal pairs.